Market Segmentation : using demographics, psychographics and other niche marketing techniques to predict and model customer behavior - Weinstein Art (Chicago, Illinios Cambridge, Probus Publishing Company, 1994)
The book was written to provide marketing practitioners and scholars with an informative, state-of- the art guide to strategically segmenting markets
Includes bibliographical references and index.
opc 31/08/16
Loans
Keywords: Marketing; Market Segmentation- Planning; United States of America